Renal parenchymal scarring and reflux nephropathy [Renal parenkimal skar ve reflü nefropatisi] - ALPAY, HARİKA; GÖKCE, İBRAHİM (My University, 2012)
Vesicoureteral reflux (VUR) is the abnormal flow of urine from the bladder into the upper urinary tract. In the majority of cases, it occurs as a result of a primary maturation abnormality of the vesicoureteral junction. When VUR is associated with bacteriuria, the possibility of pyelonephritis with subsequent renal scars increases, theoretically as a result of bacteria being more readily conveyed to the renal parenchyma. The ultimate evaluation for renal scars is done through a cortical renal scan using technetium-99 labeled dimercaptosuccinic acid. The long term complication of VUR is nephropathy. Reflux nephropathy (RN) is defined as the formation of renal parenchymal scarring and renal function impairment induced by VUR. Hypertension, proteinuria, chronic kidney disease and end stage renal failure are well-recognized sequelae of renal scars. In this review we tried to emphasize the importance of RN which is stil a significant cause of morbidity especially in developing countries.
Keywords: Hypertension; Reflux nephropathy; Renal scarring; Vesicoureteral reflux